I vantaggi e le innovazioni metodologiche del remote e del proximal sensing nel campo dell’Archeologia Preventiva - Ginacarlo Pastura (GEOmedia)
In recent years the role of preventive archaeological investigations - and consequently that of archaeologists -in territorial and urban transformation became more and more important; On the other hand, the time allocated to archaeological investigation is often severely compressed: so, it is essential to exercise targeted and effective action and, even more so, to have in-depth knowledge of the context on which the project impacts. The National Geoportal for Archaeology is a useful tool, making archaeological data available for consultation and free reuse. Its usefulness is growing every day, thanks to recent provisions that provide for the use of the GNA as a standard for the delivery of minimum data for all archaeological investigations.